Teaching business as business: The role of the case method in the constitution of management as a science-based profession. Issue 2 (14th April 2020) - Lusoli, Alberto
Abstract : Purpose: This paper aims to explore the early days of business education with the aim of understanding how the Harvard Business School (HBS) contributed to the constitution of "management" as a science-based profession. The research focuses on HBS signature pedagogy, the case method and its role in the institutionalization of managerial knowledge. Design/methodology/approach: The research is based on a qualitative content analysis of HBS Annals published between 1908 and 1930. Through a manual coding of the Annals, the paper traces the diffusion of the case method in the curriculum and connects it with the institutional transformations that took place between 1908 and 1930. Findings: The data show how HBS curriculum transitioned from lectures to case teaching in the aftermath of First World War. This pedagogy allowed HBS to demonstrate the possibility of systematically investigate management problems and to deliver business education at scale. The discussion argues that the case method, acting as a boundary object between business praxis and management theories, constituted management as a science-based profession. Originality/value: Recent debates have emerged about case method's ability to critically question socio-economic structures within which business is conducted. This paper contributes to the debate arguing that the historical and institutional factors leading to the affirmation of this pedagogical approach had a substantive role in the type of knowledge produced through its application. The findings challenge the idea that the affirmation of the case method is attributable to its epistemological primacy in investigating business problems.